\(x=\cfrac{√7+√3}{√7-√3}\) এবং \(xy=1\) হলে, দেখাই যে, \(\cfrac{x^2+xy+y^2}{x^2-xy+y^2}= \cfrac{12}{11}\)


যেহেতু, \( xy=1\)
\(∴ y=\cfrac{1}{x}\)
\( =\cfrac{√7-√3}{√7+√3}\)

\(∴ x+y= \cfrac{√7+√3}{√7-√3}+ \cfrac{√7-√3}{√7+√3}\)
\(=\cfrac{(√7+√3)^2+(√7-√3)^2}{(√7-√3)(√7+√3)}\)
\(=\cfrac{2[(√7)^2+(√3)^2]}{(√7)^2-(√3)^2)}\)
\(=\cfrac{2(7+3)}{7-3}\)
\(=\cfrac{20}{4}=5\)

এখন, \(\cfrac{x^2+xy+y^2}{x^2-xy+y^2}\)
\(=\cfrac{x^2+y^2+xy}{x^2+y^2-xy}\)
\(=\cfrac{(x+y)^2-2xy+xy}{(x+y)^2-2xy-xy}\)
\(=\cfrac{(x+y)^2-2xy+xy}{(x+y)^2-2xy-xy}\)
\(=\cfrac{(x+y)^2-xy}{(x+y)^2-3xy}\)
\(=\cfrac{(5)^2-1}{(5)^2-3×1}\) [\(x+y=5\) এবং \(xy=1\) বসিয়ে পাই]
\(=\cfrac{25-1}{25-3}\)
\(=\cfrac{24}{22}\)
\(=\cfrac{12}{11}\) [প্রমাণিত]

Similar Questions